You can't just bring people here and then not feed them: A case in support of Indigenous-led training environments. Issue 1 (March 2023) - Ambtman-Smith, Vanessa; Wysocki, Koral; Bomberry, Victoria; Reitmeier, Veronica; Nightingale, Elana
By and large, academic research in geography has advanced the colonial project, and been synonymous with extractive and reductionist research practices that subjugate Indigenous people. To counteract these harmful impacts and produce research that supports the needs of communities, advancing Indigenous sovereignty over research is vital. By presenting a case study of an Indigenous research space at a Canadian University, we argue that Indigenous training environments are more than a shared, physical space; they provide essential emotive and relational spaces of collaborative learning, wherein trainees practice relationship-building, reciprocity, and accountability. This article argues that decolonizing academic spaces dedicated to Indigenous geographic research will be essential to meeting the ethical imperative of Indigenous control over knowledge production. There is a current deficit of culturally appropriate spaces that support both the whole person and their learning. We highlight the impact of Indigenous training environments in nurturing respectful, long-standing relationships with peers, community, and research partners; a critical element of Indigenous geographies, yet one of the most challenging aspects of upholding meaningful and decolonizing research. By drawing on our diverse perspectives and research projects, we reflect on how an Indigenous-led training environment, rooted in Indigenous ways of knowing, can contribute to relational accountability both within and outside of these spaces. As more communities assert their authority over these processes, the need for respectful research grows, and it is anticipated that this article will provide a useful guide and support for emerging Indigenous training environments.